Kajian Pembuatan Xilitol dari Tongkol Jagung Melalui Proses Fermentasi - Sirin Fairus; Ronny Kurniawan; Ridho Taufana; Adhytia Setya Nugraha (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2013)
One of the substitute for sucrose is xylitol. Xylitol is a sweetener that has excellent properties for food development and pharmaceutical products. Xylitol can be obtained from the hydrolysis of xylan into xylose, and then converted into xylitol with fermentation by using Candida tropicalis yeast. Corn cob as agricultural waste is one important source of xylose because xylan content in range of 12.4 to 31.94%. The success of the fermentation reaction is influenced by several operating parameters, such as raw material type, the type of yeast used, the ratio of raw materials for fermentation reactions, temperature, pH conditions, and time. Xylitol production in this research was conducted through several stages such as pretreatment of raw material, hydrolysis, xylose treatment, and fermentation. Corn cobs were used as raw material for source of xylan. The variables of fermentation were time and temperature i.e 12, 24, 36, and 48 hours and 30, 34, and 37oC respectively. This research revealed that the optimum condition applied at 30oC and 48 hours with yield 0.558 g xylitol/g xylose. It showed that the effective growth of Candida tropicalis occur at 30oC and 48 hours.